Employee Placement System in Structural Positions in the Personnel and Human Resources Development Agency of Southeast Minahasa Regency - Tumiwan, Hence Erwin; Mandagi, Marthinus; Pangkey, Itje (Technium Social Sciences Journal, 2021)
The purpose of this study was to determine the system for placing employees in structural positions as well as the determinants of the placement of employees in structural positions in the Personnel and Human Resources Development Agency of Southeast Minahasa Regency. Data collection techniques were collected through 1) Observation, 2) Interviews, 3) Documentation. The research results are the Employee Placement System in Structural Positions through a standard mechanism, namely using Government Regulation Number 11 of 2017 concerning the Management of the State Civil Apparatus. Placement of employees in structural positions is carried out based on the principle of professionalism by the competence, work performance, ranks assigned to the position as well as other objective requirements regardless of gender, ethnicity, religion, race, or class as well as the Determinant Factors on Employee Placement, namely: 1) Academic Achievement, 2) Experience, 3) Physical and Mental Health, 4) Marital Status, 5) Age.